Neurofilament Light Chain as Biomarker for Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Verde, Federico; Otto, Markus; Silani, Vincenzo (Frontiers in Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are two related currently incurable neurodegenerative diseases. ALS is characterized by degeneration of upper and lower motor neurons causing relentless paralysis of voluntary muscles, whereas in FTD progressive atrophy of frontal and temporal lobes of the brain results in deterioration of cognitive functions, language, personality, and behaviour. Differently from Alzheimer’s disease (AD), ALS and FTD still lack a specific neurochemical biomarker reflecting neuropathology ex vivo. However, in the past 10 years considerable progress has been made in the characterization of neurofilament light chain (NFL) as cerebrospinal fluid (CSF) and blood biomarker for both diseases. NFL is a structural component of the axonal cytoskeleton and is released into the CSF as a consequence of axonal damage or degeneration, thus behaving in general as a relatively nonspecific marker of neuroaxonal pathology. However, in ALS the elevation of its CSF levels exceeds that observed in most other neurological diseases, making it useful for the discrimination from mimic conditions and potentially worthy of consideration for introduction into diagnostic criteria. Moreover, NFL correlates with disease progression rate and is negatively associated with survival, thus providing prognostic information. In FTD patients, CSF NFL is elevated compared to healthy individuals and, to a lesser extent, to patients with other forms of dementia, but the latter difference is not sufficient to enable a satisfying diagnostic performance at individual patient level. However, also in FTD CSF NFL correlates with several measures of disease severity. Due to technological progress, NFL can now be quantified also in peripheral blood, where it is present at much lower concentrations compared to CSF, thus allowing less invasive sampling, scalability, and longitudinal measurements. The latter have promoted innovative studies demonstrating longitudinal kinetics of NFL in presymptomatic individuals harbouring gene mutations causing ALS and FTD. Especially in ALS, NFL levels are generally stable over time, which, together with their correlation with progression rate, makes NFL an ideal pharmacodynamic biomarker for therapeutic trials. In this review we illustrate the significance of NFL as biomarker for ALS and FTD and discuss unsolved issues and potential for future developments.